The Mixed-Valence Catena-Heteropolycation (Bi2S2)+ - Knies, Maximilian; Nawroth, Paul; Golub, Pavlo; Isaeva, Anna; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2021)
The reaction of Bi and Bi2S3 in the Lewis-acidic ionic liquid [BMIm]Cl ⋅ 4.3AlCl3 (BMIm=1-n-butyl-3-methylimidazolium) at 200 °C yielded air-sensitive black crystals of (Bi2S2)[AlCl4]. X-ray diffraction on single-crystals revealed a monoclinic structure containing infinite chains (Formula presented.). These polycations contain bismuth(II,III) and sulfur(-II) atoms, connected by polar covalent Bi−S and Bi−Bi bonds. The assignment of bonds is ambiguous as a distinction between primary and secondary interactions is arbitrary based on interatomic distances. A real-space quantum chemical bonding analysis, including delocalization indices, helped to quantify the interactions and charge distribution, confirming that a simple Lewis formula is inappropriate to describe the polycation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: catena compounds; chemical bonding; ionothermal synthesis; mixed valence compounds; polycations